2020
DOI: 10.1021/acsomega.0c01901
|View full text |Cite
|
Sign up to set email alerts
|

Calcined Layered Double Hydroxides: Catalysts for Xanthene, 1,4-Dihydropyridine, and Polyhydroquinoline Derivative Synthesis

Abstract: This work is generally focused on the synthesis of NiFeTi-layered double hydroxides (LDHs) using a hydrothermal route, which were calcined at various temperatures (varying from 200 to 600 °C). The synthesized materials were physicochemically characterized. Xray diffraction results revealed the loss of the layered structure on calcination resulting in the formation of layered double oxides (LDOs) or mixed metal oxides, which was also supported by Fourier transform infrared studies. Scanning electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The so-formed second intermediate further reacts with ammonium acetate to form enamine, which further results in the desired product after intramolecular cyclization and dehydration steps. 13 …”
Section: Resultsmentioning
confidence: 99%
“…The so-formed second intermediate further reacts with ammonium acetate to form enamine, which further results in the desired product after intramolecular cyclization and dehydration steps. 13 …”
Section: Resultsmentioning
confidence: 99%
“…A control experiment lumpish that no product was obtained when the reaction was accomplished in the absence of the catalyst (Table 1, entry 9). The effect of different temperatures was also examined on the model reaction progress (Table 1, entries [12][13][14] and found that the multi-component reaction proceeded surprisingly at 45 C (Table 1, entry 3). It is noteworthy that the MCR reaction has a small efficiency without temperature conditions (entry 12).…”
Section: The Magnetic Catalyst Activity Of Fe 3 O 4 @Nfc@nnsm-mn(iii)mentioning
confidence: 99%
“…As a result, 40 C was selected as the optimum reaction temperature. Further investigation disclosed that the number of oxidizing agents is crucial to the product yield (entries [13][14]. When the oxidation of the model reaction was carried out using 1, 2, and 3 mmol of tert-butyl hydroperoxide, the product's yield increased as the concentration of tert-butyl hydroperoxide increased.…”
Section: The Magnetic Catalyst Activity Of Fe 3 O 4 @Nfc@nnsm-mn(iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…40 Various members of this family are currently used for cytostatic and antitumor activities (for example, nitracrine derivatives), 41 platelet antiaggregatory activities, the treatment of Alzheimer's disease, strong anti-cancer treatments (for example, amsacrine derivatives), cardiovascular diseases including hypertension and diabetes, and so on. 41,42 The structures of some xanthene and acridine derivatives are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%